The Impact of Entrepreneurial Characteristics on Bribery Incidence in Transition Economies - Phan Anh Tu, (Asian Academy of Management Journal, 2012)
Entrepreneurs in Asian economies face many difficulties in starting up and running their businesses. Relationships with government officials help to, e.g., mobilise resources and cope with the constraints imposed by bureaucratic structures. In this context, bribery can be regarded as an investment that entrepreneurs need to make in order to operate successfully in an institutionally weak transition economy. However, not all entrepreneurs pay a bribe. In this paper the relationship between demographic characteristic and bribery incidence has been investigated. This relationship was estimated using unique data derived from a survey of 606 Vietnamese entrepreneurs. The author controlled for various organisational and industrial characteristics. The exploratory results show that in particular well-educated entrepreneurs are more inclined to bribe than others.